Aluminum Complexation with Malate within the Root Apoplast Differs between Aluminum Resistant and Sensitive Wheat Lines - Kopittke, Peter M.; McKenna, Brigid A.; Karunakaran, Chithra; Dynes, James J.; Arthur, Zachary; Gianoncelli, Alessandra; Kourousias, George; Menzies, Neal W.; Ryan, Peter R.; Wang, Peng; Green, Kathryn; Blamey, F. P. C. (Frontiers in Plant Science, 2017)
In wheat (Triticum aestivum), it is commonly assumed that Al is detoxified by the release of organic anions into the rhizosphere, but it is also possible that detoxification occurs within the apoplast and symplast of the root itself. Using Al-resistant (ET8) and Al-sensitive (ES8) near-isogenic lines of wheat, we utilized traditional and synchrotron-based approaches to provide in situ analyses of the distribution and speciation of Al within root tissues. Some Al appeared to be complexed external to the root, in agreement with the common assumption. However, root apical tissues of ET8 accumulated 4- to 6-times more Al than ES8 when exposed to Al concentrations that reduce root elongation rate by 50 % (3.5 µM Al for ES8 and 50 µM for ET8). Furthermore, in situ analyses of ET8 root tissues indicated the likely presence of Al-malate and other forms of Al, predominantly within the apoplast. To our knowledge, this is the first time that X-ray absorption near edge structure (XANES) analyses have been used to examine the speciation of Al within plant tissues. The information obtained in the present study is important in developing an understanding of the underlying physiological mode of action for improved root growth in systems with elevated soluble Al.